Whole Genome Sequencing (WGS) Analysis of Virulence and AMR Genes in Extended-Spectrum β-Lactamase (ESBL)-Producing Escherichia coli from Animal and Environmental Samples in Four Italian Swine Farms - Miryam Bonvegna; Laura Tomassone; Henrik Christensen; John Elmerdahl Olsen (MDPI AG, 2022)
Whole genome sequencing (WGS) is a powerful tool to analyze bacterial genomes rapidly, and can be useful to study and detect AMR genes. We carried out WGS on a group of Escherichia coli (n = 30), sampled from healthy animals and farm environment in four pigsties in northern Italy. Two × 250bp paired end sequencing strategy on Illumina MiSeq™ was used. We performed in silico characterization of E. coli isolates through the web tools provided by the Center for Genomic Epidemiology (cge.cbs.dtu.dk/services/) to study AMR and virulence genes. Bacterial strains were further analyzed to detect phenotypic antimicrobial susceptibility against several antimicrobials. Data obtained from WGS were compared to phenotypic results. All 30 strains were MDR, and they were positive for the genes blaCTX-M and blaTEM as verified by PCR. We observed a good concordance between phenotypic and genomic results. Different AMR determinants were identified (e.g., qnrS, sul, tet). Potential pathogenicity of these strains was also assessed, and virulence genes were detected (e.g., etsC, gad, hlyF, iroN, iss), mostly related to extraintestinal E. coli pathotypes (UPEC/APEC). However, enterotoxin genes, such as astA, ltcA and stb were also identified, indicating a possible hybrid pathogenic nature. Various replicons associated to plasmids, previously recovered in pathogenic bacteria, were identified (e.g., IncN and IncR plasmid), supporting the hypothesis that our strains were pathogenic. Eventually, through WGS it was possible to confirm the phenotypic antibiotic resistance results and to appreciate the virulence side of our ESBL-producing E. coli. These findings highlight the need to monitor commensal E. coli sampled from healthy pigs considering a One Health perspective.